Moderating effect of PLIN4 genetic variant on impulsivity traits in 5-year-old-children born small for gestational age. (October 2018) - Rodrigues, Danitsa Marcos; Manfro, Gisele Gus; Levitan, Robert Daniel; Steiner, Meir; Meaney, Michael Joseph; Silveira, Patrícia Pelufo
Highlights: A allele of the rs8887 SNP ( PLIN4 gene) is associated with increased responsiveness to consumed n-3 PUFAs. We found an interaction between fetal growth and presence of the A allele on a inhibitory control task, demonstranting that lower birth weight is associated wtih poor inhibitory control only in the non-carriers individuals. Dietary n-3 PUFAs in infancy may protect small for gestional age children developing impulsive behaviors. Abstract: Poor fetal growth is associated with long-term behavioral, metabolic and psychiatric alterations, including impulsivity, insulin resistance, and mood disorders. However, the consumption of omega-3 polyunsaturated fatty acid (n-3 PUFA) seems to be protective for this population, improving inhibitory control and behavioral reactivity. We investigated whether the presence of the A allele of rs8887 SNP ( PLIN4 gene), known to be associated with increased sensitivity to the consumption of n-3 PUFAs, interacts with fetal growth influencing inhibitory control. 152 five-year-old children were genotyped and performed the Stop Signal Task (SSRT). There was a significant interaction between birth weight and the presence of the A allele on SSRT performance, in which lower birth weight associated with poorer inhibitory control only in non-carriers. These results suggest that a higher responsiveness to n-3 PUFAS protects small for gestational age children from developing poor response inhibition, highlighting that optimizing n-3 PUFA intake may benefit this population.